Unveiling the black box: exploring teachers’ approaches to ethnic victimization incidents at school - Bayram Özdemir, Sevgi; Özdemir, Metin (Frontiers in Education, 2024)
Schools are crucial socialization contexts where civic norms and values such as appreciating diverse perspectives and embracing differences can be systematically transmitted to the next generations. This process, in turn, can foster the development of more inclusive societies. However, increasing polarized political climate poses a risk for the formation of harmonious interactions between youth of different ethnic origins in schools. Teachers are considered as crucial resources in addressing negative student interactions and helping victims in overcoming the consequences of their negative experiences. Nevertheless, our understanding of how teachers respond to ethnic victimization incidents is limited, along with the factors influencing their responses. To address this gap in knowledge, we examined the relative contributions of teachers’ general efficacy (i.e., managing disruptive behaviors in class) and diversity-related efficacy (i.e., addressing challenges of diversity) on their responses to ethnic victimization incidents. The sample consisted of head teachers of 8th grade students (N = 72; 56% females). The results showed that teachers adopt a diverse range of strategies to address incidents of ethnic victimization, with a primary focus on prioritizing the comfort of the victim as the foremost action. Further, we found that teachers’ efficacy in handling disruptive behaviors in class, as opposed to their efficacy in addressing diversity-related issues, explained their responses to victimization incidents. Specifically, teachers with a high sense of efficacy for classroom management were more likely to contact parents of both victims and perpetrators and to provide comfort to the victim. These findings highlight the necessity of supporting teachers to enhance their efficacy in classroom management, and in turn to address potential challenges in diverse school settings more effectively.